Reading Habit and Its Affect on Academic Performance of The Students of Advanced Technological Institute, Sammanthurai - Firnas, Abul; Munas; Rizvi, Mohammed (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Readings plays an important role in the life of a human. It is also one of the most important components of the language. Reading habit is determined by measuring how often the people read, how long do they read and what do they read. Particularly for students, reading is very crucial part for them during the span of learning. It is an instrument used to acquire new knowledge and skills. This study aims to investigate the reading habits among students and their effect on their academic performance. This study is conducted at ATI, Sammanthurai located in the Eastern province, Sri Lanka. Data are collected using questionnaire with deductive approach in quantitative method and analyzed by statistical package for social science (SPSS). Findings are presented using frequency analysis, regression analysis, descriptive analysis and correlation analysis. The questionnaire is conducted via Google form then shared among the students of ATI, Sammanthurai. The findings indicate that most of the students has a good reading habit and it affects their academic performance positively. Finally, the study confirms that there is a relationship between reading habit and the academic performance of the students. Some findings are that; the majority of the respondents read class notes which means the need to read it for the examination purpose. Majority of the students get reading material via internet (81.4%) as they state that they spend most of their time in surfing internet and using social media.